2014
DOI: 10.1097/cmr.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Response rate to vemurafenib in patients with B-RAF-positive melanoma brain metastases

Abstract: The intracerebral response rate (RR) to vemurafenib in patients with B-RAF mutated melanoma brain metastasis was assessed. Patients with B-RAF-positive metastatic melanoma and asymptomatic brain metastases at initiation of vemurafenib were eligible. Records were analysed retrospectively to calculate the RR, duration of responses, time to central nervous system (CNS) progression and overall survival. Twenty-two patients with CNS metastasis received vemurafenib (male : female=13 : 9; median age 49); 12 had recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
1
20
0
1
Order By: Relevance
“…The physiochemical properties of vemurafenib including its hydrophilic and hydroscopic nature also would suggest its limited distribution in the brain [18,19]. However, vemurafenib has shown some activity in established brain metastases in some case reports and observational studies [7][8][9][10]. In addition, our retrospective review of patients who developed brain metastases during the study period showed that vemurafenib decreased the incidence of brain lesions in patients treated with the drug before the development of brain lesions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The physiochemical properties of vemurafenib including its hydrophilic and hydroscopic nature also would suggest its limited distribution in the brain [18,19]. However, vemurafenib has shown some activity in established brain metastases in some case reports and observational studies [7][8][9][10]. In addition, our retrospective review of patients who developed brain metastases during the study period showed that vemurafenib decreased the incidence of brain lesions in patients treated with the drug before the development of brain lesions.…”
Section: Discussionmentioning
confidence: 88%
“…However, patients with brain metastases were excluded from the pivotal vemurafenib study [6]. As a result, information on the impact of BRAF inhibitors on brain metastases is based mostly on single case reports or small case series [7][8][9][10]. In addition, the effect of BRAF on the risk of developing brain metastases is not well known [11].…”
Section: Introductionmentioning
confidence: 99%
“…While data of the first studies did not allow drawing conclusions on vemurafenib intra-cerebral efficacy, various studies have shown in patients with V600E mutation an intracranial response rate of 16-50 %, with a progression-free survival of 3.9-4.6 months and an overall survival of 5-8 months, increased up to 13.7 months in a series of 12 patients in association with radiotherapy. The 6-month local control rate was of 75 % in this series [7,25,[28][29][30]. Patients with V600K mutation seem to be less responsive with an estimated progression-free survival of 2-4 months and overall survival of 4-5 months.…”
Section: Discussionmentioning
confidence: 94%
“…Dans une autre cohorte, l'effet du vĂ©murafĂ©nib Ă©tait analysĂ© chez 22 patients avec mĂ©lanome BRAF mutĂ© et mĂ©tastases cĂ©rĂ©-brales asymptomatiques [34]. Dans la cohorte A, les 12 patients n'ont pas reç u de traitement local prĂ©alablement, quatre patients atteints d'une maladie cĂ©rĂ©brale progressive aprĂšs traitement local ont Ă©tĂ© Ă©galement inclus dans cette cohorte.…”
Section: Tableauunclassified